WORKSHOP PENDAMPINGAN BISNIS TEKNOLOGI CERDAS “SMART TRASH BIN” DESA KESAMBEN, KECAMATAN NGAJUM, MALANG, INDONESIA - Dura, Justita; Cahyaningtyas, Fadilla; Yogatama, Ahmad Nizar; Bukhori, Mohammad; Hanif, Rifki; Aqromi , Nur Lailatul; Afiyah, Siti Nurul; Riska, Suastika Yulia; Farokah, Lia; Arifin, Jaenal; Islamiyah, Mufidatul; Arifin, Samsul; Jatmika, Sunu (Yayasan Education and Social Center, 2024)
Kesamben Village, Ngajum District, Malang Regency faces serious problems in waste management that have an impact on the environment and public health. This community service program aims to introduce